Systems Design, Fabrication, and Testing of a High-Speed Miniature Motor for Cryogenic Cooler - Dipjyoti Acharya; Lei Zhou; Liping Zheng; Thomas X. Wu; Jay Kapat; Louis Chow; Nagaraj K. Arakere (International Journal of Rotating Machinery)
The long-term storage of liquid hydrogen for space missions is of considerable interest to NASA. To this end, the Reverse Turbo-Brayton Cryocooler (RTBC) is considerably lighter than conventional designs and a potentially viable and attractive solution for NASA's long-term Zero-Boil-off (ZBO) hydrogen storage system for future space missions. We present the systems design, fabrication, and performance evaluation of the Permanent Magnet Synchronous Motor (PMSM) powering a cryocooler capable of removing 20 W of heat at 18 K with a COP of 0.005 and driven by two 2-kW permanent magnet synchronous motors operating at 200 000 rpm and at room temperature and 77 K. Structural, thermal, and rotordynamic aspects of system design are considered.